Community environmental education and the struggle for water - Pelacani, Bárbara; Kassiadou, Anne; Camargo, Daniel Renaud; Sánchez, Celso; Stortti, Marcelo (Universidad Pedagógica y Tecnológica de Colombia, 2021)
In this article, we propose to reflect on the environmental education that emerges from the conflict over the construction project of the Guapiaçu dam, in Cachoeiras de Macacu, Rio de Janeiro. To this end, we start from the perspective of community environmental education developed by the Environmental Education Study Group from the South, especially in the interaction with the Movement of Dam Affected People, for the pursuit of environmental justice. Thus, such meetings unveil the necropolitical bias of this “development” project, that clashes with farmers and with life in this territory. Therefore, we highlight the communityenvironmental education, interwoven from the encounter with the voices and the waters that flow through this environment, as a possible way to confront a necropedagogy that supports such necropolitics.